Determination of Listeria, Salmonella, E.coli type 1, and K.pneumoniae in ice cream samples marketed in Elazi? - Arslan, Ali; Gönülalan, Zafer; Ateş, Gülsüm; Güven, Abamüslüm (Scientific and Technical Research Council of Turkey, 1996)
This study was performed to study for the presence of E.coli type 1. K.pneumoniae. Listeria and Salmonella species in Ice cream samples marketed in Elazi?. Of 73 samples examined. 22 (30.13 %) had E.coli type 1. The numbers of samples containing K.pneumoniae. E.coli type 1 + K.pneumoniae. E.coli type 1 + K.pneumoniae + Listeria. E.coli type 1 Listeria were 18 (24.65 %), 30 (41.19 %). 1 (1.36 %), 1 (1.36 %) respectively. Two samples had Listeria species. The result of identification of Listeria species have shown that all (s) isolates in the first sample belonged to L.monocytogenes. In the second sample 3 isolates were L.monocytogenes. one of the remaining isolates belonged to L.monocua and the other was Lgrayii. All samples were negative for Salmonella. The result of this study indicates that ice cream samples marketed at Elazi? region do not meet microbiological quality standarts required for consumer health.
Elazi?'da Tüketime Sunulan Dondurmalarda Listeria, Salmonella, E.coli Tip 1 ve K.pneumoniae'nm Araştirilmasi
Keywords: E.coli type 1; Ice Cream; K.pneumoniae; Listeria; Salmonella